Validation of Instrument Multiple Representations for Analyzing the Multiple Representations Capability of Students in Hydrocarbon Materials - Antonia Fransiska Laka; Hari Sutrisno (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2021)
This study aims to validate multiple representational instruments to analyze the ability of multiple representations of students on hydrocarbon material. This research uses a descriptive quantitative method with a non-experimental approach. This research uses the stratified purposive sampling method with 123 students who will respond to 35 items of multiple-choice questions covering macroscopic, microscopic, symbolic, and mathematical aspects. The data analysis technique used in the research is qualitative data analysis and quantitative data analysis. The Rasch model in this research analyzed instruments such as unidimensionality, item fit, test reliability, and difficulty level of the item. The data analysis shows that the average Aiken index is 0.961 on the substance aspect, 0.93 on the construction aspect, and 0.950 on the language aspect for the theoretical validation results. The highest Aiken index is 1.000, and the lowest is 0.896. Unidimensionality was 32.4%, the result of the item fit analysis obtained 1 item that was not fit, namely item number 29, and for the reliability test results: the person reliability value was 0.65, and the item reliability was 0.97. The analysis results of the difficulty level of the items on the instrument of measuring the cognitive abilities of students with multiple representations types were nine items in the easy category, 14 items in the medium category, and 11 items in the difficult category. Therefore, based on the resulting validity and reliability categories, the compiled test instrument can be used as a tool to measure students’ multiple representation abilities.